Predicting Chikungunya disease personal protective behaviors: Results of a cross-sectional survey of US-Caribbean travelers - Kristina R Anderson; Kevin Naaman; Edna Omodior; Grace Karikari; Lori Pennington-Gray; Oghenekaro Omodior (Tabriz University of Medical Sciences, 2020)
Background: Incidents of vector-borne disease have recently tripled in the United States. Chikungunya disease is a particularly common disease in the Caribbean, posing a threat to international tourists. However, the relationship between psychological variables derived from the protection motivation theory (PMT), and adoption of protective behaviors against the disease, is uncertain. This study sought to identify the psychological predictors of travelers' protective health behaviors, specifically (1) appropriate clothing use, and (2) indoor spatial repellent use. Methods: An online, retrospective survey of U.S. international travelers to Caribbean destinations measured the five constructs of the PMT in the context of Chikungunya disease: Perceived severity, perceived vulnerability, perceived response efficacy, perceived self-efficacy, and knowledge. Hierarchical logistic regression analyzed whether these five theoretical constructs predicted the two protective behaviors in respondents who met study criteria (n = 184). Results: Results suggest that the interaction between chikungunya knowledge and perceived chikungunya severity predicts both appropriate clothing use (odds ratio [OR]: 1.95, CI: 1.18-3.25, P=0.010) and indoor spatial repellent use (OR: 1.55, CI: 1.05-2.29, P=0.029). In the cases of appropriate clothing use, the interaction between perceived chikungunya severity and perceived vulnerability was also a significant predictor (OR: 9.67, CI:1.23-75.80, P=0.031). Additionally, indoor spatial repellent use was also predicted by the interaction of chikungunya knowledge and perceived vulnerability (OR: 1.88, CI:1.18-3.02, P=0.009). Conclusion: Two-pronged educational approaches may be most efficacious in increasing protective health behaviors. Such efforts could reduce incidents of chikungunya disease and other vectorborne diseases in travel destinations featuring high exposure risks.